Desenvolvimento de metodologia para eletrodegradação de ciprofloxacina por agentes oxidantes gerados in situ - Silva, Jaime Rodrigues da (2012)
Environmental contamination by drugs of antibiotic action can bring as a consequence the development of more resistant bacteria, altering the microbial community structure in nature. Due to its widespread use, ciprofloxacin has been identified in trace concentrations in sewage treatment plants (STPs) and surface waters, since the conventional processes of wastewater treatment does not remove the usual drugs completely, these substances have been detected in drinking water, which represents a direct risk to humans, since the constant contamination of water may be associated with the continuous process and reuse of the water increasing worldwide. In this study, a method of electrochemical oxidation of ciprofloxacin, since the transfer of electrons, drugs can be processed, biodegraded or mineralized. The electrochemical oxidation of the drugs can occur in a satisfactory manner, the surface of some anode metal oxide, capable of generating oxygen and simultaneously with the formation of higher oxides or superoxide. This mechanism is at the surface of ADE ® coated and immobilized metal oxides. To identify and monitor the change in concentration of ciprofloxacin was analyzed their absorption spectra in the ultraviolet and visible (200-800 nm). Ciprofloxacin in aqueous solution shows two absorption peaks in completely different bands and with maximum at 270 nm and 315 nm. The nature of the electrolyte and the pH had great influence on the speed of the degradation process. In the midst of Cl- was a more efficient degradation. In studies with HCl, NaCl and KCl was observed 100% removal of the yellow color characteristic of the presence of Cl-anion and subsequent formation of hypochlorite (ClO-). In turn, the pH was a limiting factor in this process, where it was observed that the reaction proceeds in most satisfactorily at pH values below 4.0. The current that showed the best result was 80 mA. The method of supplying water to said acid chloride in ciprofloxacin can be completely degraded within 5 min.